2021
DOI: 10.14336/ad.2021.0304
|View full text |Cite
|
Sign up to set email alerts
|

cGAS- Stimulator of Interferon Genes Signaling in Central Nervous System Disorders

Abstract: Cytosolic nucleic acid sensors contribute to the initiation of innate immune responses by playing a critical role in the detection of pathogens and endogenous nucleic acids. The cytosolic DNA sensor cyclic-GMP-AMP synthase (cGAS) and its downstream effector, stimulator of interferon genes (STING), mediate innate immune signaling by promoting the release of type I interferons (IFNs) and other inflammatory cytokines. These biomolecules are suggested to play critical roles in host defense, senescence, and tumor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 182 publications
(162 reference statements)
0
11
0
Order By: Relevance
“…STING is a dimeric transmembrane protein at the endoplasmic reticulum (ER) with 42-kDa ( 14 ). Research on the immune role of the STING pathway in CNS disorders has grown in recent years ( 34 , 36 , 37 ). However, little is known about the role of STING in the pathological process of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…STING is a dimeric transmembrane protein at the endoplasmic reticulum (ER) with 42-kDa ( 14 ). Research on the immune role of the STING pathway in CNS disorders has grown in recent years ( 34 , 36 , 37 ). However, little is known about the role of STING in the pathological process of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that STING is an essential immune response and nociception in neurons (Flood et al, 2019;Gui et al, 2019;Liu et al, 2019a;McLaughlin et al, 2020;Donnelly et al, 2021). Studies suggested that STING contributes to ER stress and several diseases (Smith, 2020;Zhang et al, 2020;Li et al, 2021). Our data suggested that excess and prolonged elevated p-STING neutralized the ketamine-induced benefits in SNL rats.…”
Section: Discussionmentioning
confidence: 49%
“…No study has investigated which nerve cells play a main role in the activation of cGAS–STING pathways. Many studies of CNS injury suggest that microglia are the principal innate immune cells in the brain and the first responders to pathological insults and produce high levels of type I IFN [ 74 , 75 ]. Currently, most research focuses on the role of microglia in the activation of cGAS–STING pathways in CNS injury [ 76 , 77 ].…”
Section: Sting Signalling In Cns Injuriesmentioning
confidence: 99%